Bio-based coating for prolonging durability of concrete surface in high-cold and high-altitude areas

By using improved bio-based coatings on concrete surfaces in high-altitude areas, combined with impregnated bio-based silicone and hydrophobic silicon biomicrospheres, the freeze-thaw damage and mold breeding problems of concrete structures are solved, significantly improving the problem of cold-thawing and mold growth of concrete structures, It has durability and freeze-thaw resistance, and is suitable for engineering structures in high-altitude areas.

CN119220175APending Publication Date: 2024-12-31CHONGQING JINHONG CONSTR ENG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411519602.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Concrete structures in high-altitude areas are prone to freeze-thaw damage and mold breeding problems due to insufficient water pressure resistance and low-thaw resistance. The existing coatings age and crack after outdoor exposure, which affects the protection performance.

Method used

Using a bio-based coating including impregnated bio-based silicone, hydrophobic silicon biomicrospheres, inorganic fillers, anti-aging agents and bio-based composite antibacterial agents, the adhesion of the coating is enhanced by improving the composition and preparation method of the coating. , hydrophobicity and anti-freeze-thaw properties, reduce water absorption and prevent mold growth.

Benefits of technology

It significantly improves the durability and freeze-thaw resistance of the concrete surface, reduces water absorption, extends service life, prevents the growth of mold and moss, and maintains the transparency and protective performance of the concrete appearance. It is suitable for engineering structures in high-altitude areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005107674490000091
    Figure BDA0005107674490000091
  • Figure BDA0005107674490000101
    Figure BDA0005107674490000101
  • Figure BDA0005107674490000102
    Figure BDA0005107674490000102
Patent Text Reader

Abstract

The invention discloses a bio-based coating for prolonging the durability of a concrete surface in a high-cold and high-altitude area, and the coating comprises the following components in parts by weight: 20-30 parts of impregnated bio-based siloxane, 1-2 parts of a silicon coupling agent, 10-20 parts of hydrophobic silicon biological microspheres, 15-20 parts of deionized water, 20-35 parts of an inorganic filler and 5-15 parts of an auxiliary agent, the invention relates to an antibacterial coating which comprises the following components in parts by weight: 1-5 parts of an antioxidant, 1-5 parts of an anti-aging agent, 1-5 parts of trimethylpentyltriethoxysilane, 1-5 parts of a bio-based composite antibacterial agent and 10-30 parts of an organic solvent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of coatings for the concrete durability protection industry, and specifically to a bio-based coating for extending the durability of concrete surfaces in high-cold and high-altitude areas. Background Art

[0002] In high-altitude and cold regions, the main reason for concrete damage is insufficient water pressure resistance and freeze-thaw durability. my country has a vast territory, and a considerable part of the country is in severe cold zones, and many bridges and hydraulic structures have experienced freeze-thaw damage.

[0003] Freeze-thaw damage to concrete structures or structures in hydraulic engineering, port engineering, roads and bridges in cold regions under the action of freeze-thaw cycles is the main disease in the operation process of these structures. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of this application is to provide a bio-based coating that can extend the durability of concrete surfaces in cold and high-altitude areas, so as to solve the problems of outdoor exposure aging, freeze-thaw damage, and mold growth of concrete in the prior art.

[0005] In order to solve the above technical problems, this application adopts the following technical solutions:

[0006] A bio-based coating for extending the durability of concrete surface in cold and high altitude areas, the coating comprising the following components calculated by weight:

[0007] The impregnated bio-based siloxane is 20-30 parts, the silicon coupling agent is 1-2 parts, the hydrophobic silicon bio-microspheres are 10-20 parts, the deionized water is 15-20 parts, the inorganic filler is 20-35 parts, the auxiliary agent is 5-15 parts, the anti-aging agent is 1-5 parts, the trimethylpentyltriethoxysilane is 1-5 parts, the bio-based composite antibacterial agent is 1-5 parts, and the organic solvent is 10-30 parts.

[0008] Preferably, the impregnated bio-based siloxane is prepared by the following method:

[0009] Add isopropanol, methyltriethoxysilane, heptadecafluorodecyltrimethoxysilane, γ-aminopropyltriethoxysilane, polyoxyethylene mono-4-octylphenyl ether, ethyl orthosilicate and acetic acid to the reactor in sequence, raise the temperature to 110°C, then stir for 35 hours, reduce the temperature to 100°C, then stir for 35 hours; control the pH value to 7; reduce the temperature to 50°C, keep the temperature at this temperature for 2 hours, add the film-forming agent and continue stirring for 3 hours to obtain an impregnated bio-based siloxane;

[0010] Among them, the amount of raw materials calculated by weight is as follows: 3-5 parts of methyltriethoxysilane, 3-5 parts of heptadecafluorodecyltrimethoxysilane, 3-5 parts of γ-aminopropyltriethoxysilane, 3-5 parts of polyoxyethylene mono-4-octylphenyl ether, 3-7 parts of tetraethyl orthosilicate, 1-2 parts of acetic acid, 90-100 parts of isopropanol, and 2-3 parts of film-forming agent.

[0011] Preferably, the silicon coupling agent is one of an aminosilane coupling agent, a silicate coupling agent, a silicon oxide coupling agent, and a fluorocarbon silane coupling agent.

[0012] Preferably, the hydrophobic silica biomicrospheres are obtained by the following method:

[0013] Step 1: dissolving polyvinyl alcohol, di-tert-butyl-p-cresol and sodium sulfate in ultrapure water to prepare an aqueous phase solution; wherein the mass ratio of polyvinyl alcohol, di-tert-butyl-p-cresol and sodium sulfate is (20-25): (0.1-0.5): (0.2-0.5);

[0014] Step 2: uniformly mixing an organic peroxide initiator, vinyl chloride, divinylbenzene, D40 solvent oil and an acetylene glycol surfactant until they are completely dissolved to obtain an oil phase solution; wherein the mass ratio of the organic peroxide initiator, vinyl chloride, divinylbenzene, D40 solvent oil and the acetylene glycol surfactant is (2.5-3.0):(5-10):(1-5):(1-2):(3-5);

[0015] Step 3: Evenly disperse the oil phase in the water phase to prepare an O / W emulsion, and carry out a suspension polymerization reaction under a nitrogen atmosphere at a reaction temperature of 80 to 90° C. for a reaction time of 10 to 14 hours, and then wash and dry to obtain the hydrophobic silica biomicrospheres.

[0016] Preferably, the bio-based composite antimicrobial agent is Composite antimicrobial agent.

[0017] Preferably, the organic solvent is one or a mixture of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, halogenated hydrocarbons, alcohols, esters, ketones, and glycol derivatives.

[0018] Preferably, the inorganic filler is one or more of titanium dioxide, heavy calcium and mica; different contents are added according to the needs of the parts.

[0019] Preferably, the auxiliary agent includes a wetting agent, a dispersant and a defoaming agent; wherein the wetting agent is PE-100, the dispersant is ammonium salt dispersant 5027 or 5040 dispersant, and the defoaming agent is KMT-7033.

[0020] The present application provides a method for preparing a bio-based coating for extending the durability of concrete surfaces in cold and high altitude areas, which specifically comprises the following steps:

[0021] Step 1: uniformly mix the raw materials of the coating according to any one of claims 1 to 8;

[0022] Step 2: Apply the coating obtained by mixing in step 1 on the clean and dry concrete surface, and allow it to solidify after contact with air.

[0023] Compared with the prior art, this application has the following beneficial effects:

[0024] The coating described in the present application is colorless and transparent, and may not change the appearance of the concrete. At the same time, the coating is a semi-impregnated and film-forming coating, and may also be a decorative coating with strong covering power, integrating anti-freeze and thaw and decorative properties; and can effectively prevent the growth of mold and moss on the coating surface, and corrosion by acids and alkalis such as deicing agents (deicing salts), thereby ensuring the dryness of the concrete interior; it also greatly reduces the water absorption rate of concrete, with an expected reduction of 90 to 98%, and the number of freeze-thaw cycles is increased by 3 to 4 times, and it can withstand a static water pressure of 7 to 8 meters and a temperature of -60°C. DETAILED DESCRIPTION

[0025] This application will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on this application belong to the scope of protection of this application.

[0026] Unless otherwise indicated in specific cases in this application, the numerical ranges listed herein include the upper and lower limits, as well as all integers and fractions within the range, and are not limited to the specific values ​​listed when defining the range.

[0027] 1. A bio-based coating that extends the durability of concrete surfaces in cold and high-altitude areas

[0028] Calculated by weight, the coating described in this application includes the following components:

[0029] The impregnated bio-based siloxane is 20-30 parts, the silicon coupling agent is 1-2 parts, the hydrophobic silicon bio-microspheres are 10-20 parts, the deionized water is 15-20 parts, the inorganic filler is 20-35 parts, the auxiliary agent is 5-15 parts, the anti-aging agent is 1-5 parts, the trimethylpentyltriethoxysilane is 1-5 parts, the bio-based composite antibacterial agent is 1-5 parts, and the organic solvent is 10-30 parts.

[0030] In the process of in-depth research on existing coatings, especially in high-cold and high-altitude areas, concrete structures are easily damaged due to the influence of freeze-thaw cycles. Moreover, ultraviolet rays are often too abundant in high-cold and high-altitude areas, so that when the coatings of the prior art are used in high-cold and high-altitude areas, they are prone to aging after long-term exposure outdoors, resulting in cracking of the coating, which reduces its protective performance on the concrete surface. At the same time, the humidity in high-cold and high-altitude areas is high, and it is very easy to breed mold in the cracks of the coating in a humid environment, which not only affects the appearance, but also has an adverse effect on the performance of the concrete structure. This application considers improving the existing coatings and adopts an impregnated biosiloxane. The alkoxy functional groups in the bio-based silane undergo a hydrolysis reaction under the catalysis of water and concrete base to obtain biosilicon hydroxyl groups. Condensation reactions will further occur between the biosilicon hydroxyl groups and between the silicon hydroxyl groups and the hydroxyl groups present in the concrete to form stable silicon-oxygen-silicon chemical bonds, which enhance the adhesion of the coating and make the coating not easy to fall off and crack. At the same time, the present application also found that the addition of hydrophobic silicon bio-microspheres, due to the presence of a large number of hydrophobic groups on the surface of the microspheres, makes it possible for no water to penetrate into the gaps in the coating, thereby making the coating have a higher hydrophobic property and achieving the purpose of waterproofing; and, compounding bio-silicon coupling agents and impregnated bio-based siloxanes enhances the hydrophobicity and freeze-thaw resistance of the coating. Therefore, the coating described in the present application can reduce the water absorption rate of concrete by 95-99%, and the number of freeze-thaw cycles is greater than 250 times. It can be seen that the coating has good freeze-thaw resistance, good hydrophobicity, and is not easy to fall off. It can withstand air corrosion and environmental climate invasion for a long time, and increases the service life. It is especially suitable for concrete structures in water conservancy, port engineering, roads and bridges in high-cold and high-altitude areas. In addition, the surface impregnation coating is colorless and transparent, and does not change the appearance of the concrete. The coating is a semi-impregnated film-forming coating, which can be a transparent coating or a decorative coating with strong covering power, integrating freeze-thaw resistance and decorative properties.

[0031] In some embodiments of the present application, the impregnated bio-based siloxane is prepared by the following method:

[0032] isopropanol, methyl triethoxysilane, heptadecafluorodecyl trimethoxysilane, γ-aminopropyl triethoxysilane, polyoxyethylene mono-4-octylphenyl ether, ethyl orthosilicate and acetic acid are sequentially added to the reactor, followed by stirring for 70 to 72 hours, and controlling the pH value to be 7 to 8; then, a film-forming agent is added and stirring is continued for 3 to 4 hours to obtain an impregnated bio-based siloxane;

[0033] Among them, the raw material dosage is calculated as follows according to the weight: 3-5 parts of methyl triethoxysilane, 3-5 parts of heptadecafluorodecyl trimethoxysilane, 3-5 parts of γ-aminopropyl triethoxysilane, 3-5 parts of polyoxyethylene mono-4-octylphenyl ether, 3-7 parts of ethyl orthosilicate, 1-2 parts of acetic acid, 90-100 parts of isopropanol, and 2-3 parts of film-forming agent. According to the weight, the dosage of the impregnated bio-based siloxane is 20-30 parts. The less the dosage of the impregnated bio-based siloxane, the greater the elastic modulus and water absorption rate of the organic silicon coating, and the effect of preventing water and chloride ions from penetrating into the coating cannot be achieved; on the contrary, if the dosage is too much, the silane content will increase, and the Shore hardness and water contact angle will decrease; moreover, the excessive addition of the impregnated bio-based siloxane will increase the hydrophilic groups on the surface of the coating, reduce the water contact angle, and increase the attachment of mold and bacteria. Therefore, the amount of the impregnated bio-based siloxane can be 20 parts, 25 parts, 30 parts, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges can be combined with any other ranges.

[0034] In some embodiments of the present application, the silicon coupling agent is one or a mixture of aminosilane coupling agent, silicate coupling agent, silicon oxide coupling agent, and fluorocarbon silane coupling agent. The type of silane coupling agent will not affect the final performance of the coating, but its dosage will. Calculated by weight, the amount of silane coupling agent is 1-2 parts. When the amount of silane coupling agent is controlled within this range, it will have a significant and favorable effect on the reinforcing effect of the whiskers: too low an amount will reduce the flexural strength of the coating, affect the mechanical properties of the coating, cause the coating to crack easily, reduce adhesion, and weaken the protective effect; while too high an amount may cause excessive crosslinking within the system, which in turn affects flexibility, making the coating too hard and brittle and easy to crack when the temperature changes. Therefore, the amount of silicon coupling agent can be 1 part, 1.5 parts, 2 parts, etc., as well as all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other range.

[0035] In some embodiments of the present application, the hydrophobic silica biomicrospheres are obtained by the following method:

[0036] Step 1: dissolving polyvinyl alcohol, di-tert-butyl-p-cresol and sodium sulfate in ultrapure water to prepare an aqueous phase solution; wherein the mass ratio of polyvinyl alcohol, di-tert-butyl-p-cresol and sodium sulfate is (20-25): (0.1-0.5): (0.2-0.5);

[0037] Step 2: uniformly mixing an organic peroxide initiator, vinyl chloride, divinylbenzene, D40 solvent oil and an acetylene glycol surfactant until they are completely dissolved to obtain an oil phase solution; wherein the mass ratio of the organic peroxide initiator, vinyl chloride, divinylbenzene, D40 solvent oil and the acetylene glycol surfactant is (2.5-3.0):(5-10):(1-5):(1-2):(3-5);

[0038] Step 3: Evenly disperse the oil phase in the water phase to prepare an O / W emulsion, and carry out a suspension polymerization reaction under a nitrogen atmosphere at a reaction temperature of 80 to 90° C. for a reaction time of 10 to 14 hours, and then wash and dry to obtain the hydrophobic silica biomicrospheres.

[0039] The hydrophobic silicon bio-microspheres prepared by the above steps in the present application can be well dispersed in the coating system because of the large number of hydrophobic groups on the surface of the microspheres. On the other hand, after the coating is applied to the concrete surface, the gaps between the coatings will not be penetrated by water due to its hydrophobicity, especially in a humid environment, which can well prevent water from penetrating into the coating and causing mold. The impregnated bio-based siloxane is prepared by the following method:

[0040] Add isopropanol, methyltriethoxysilane, heptadecafluorodecyltrimethoxysilane, γ-aminopropyltriethoxysilane, polyoxyethylene mono-4-octylphenyl ether, ethyl orthosilicate and acetic acid to the reactor in sequence, raise the temperature to 110°C, then stir for 35 hours, reduce the temperature to 100°C, then stir for 35 hours; control the pH value to 7; reduce the temperature to 50°C, keep the temperature at this temperature for 2 hours, add the film-forming agent and continue stirring for 3 hours to obtain an impregnated bio-based siloxane;

[0041] Among them, the amount of raw materials calculated by weight is as follows: 3-5 parts of methyltriethoxysilane, 3-5 parts of heptadecafluorodecyltrimethoxysilane, 3-5 parts of γ-aminopropyltriethoxysilane, 3-5 parts of polyoxyethylene mono-4-octylphenyl ether, 3-7 parts of tetraethyl orthosilicate, 1-2 parts of acetic acid, 90-100 parts of isopropanol, and 2-3 parts of film-forming agent.

[0042] Calculated by weight, the amount of hydrophobic silicon biomicrospheres added is 10-20 parts. If the amount is too low, it will not prevent water from penetrating into the coating, and if the amount is too much, it will affect the dispersion effect and cause the paint film to bloom. Therefore, the amount of hydrophobic silicon biomicrospheres added can be 10 parts, 15 parts, 20 parts, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiments, any of the above ranges can be combined with any other ranges.

[0043] In some embodiments of the present application, the bio-based composite antibacterial agent is obtained by loading silver ions on submicron cubic zirconium phosphate and then combining it with titanium dioxide, zinc ions, etc. using a specific composite technology. Composite antimicrobial agent. Calculated by weight, the amount of bio-based composite antimicrobial agent is 1 to 5 parts. Too little amount will not have a bactericidal effect, which will make it easy for mold to grow on the coating surface, thereby destroying the protective effect of the coating; too much amount will destroy the bio-based activity and affect the final film-forming effect, which will cause the coating performance to be unstable, and then discoloration, peeling and other phenomena will occur, especially in high-cold and high-altitude areas. Due to the unstable temperature in these areas, the fluctuation range is large. Once the coating performance is unstable, when encountering a sudden change in temperature, the coating surface will change color in a short time, as well as a considerable number of cracks, thereby affecting the protective effect of the coating. Therefore, the amount of bio-based composite antimicrobial agent can be 1 part, 3 parts, 5 parts, etc., as well as all ranges and sub-ranges between the above values. It should be understood that in the implementation plan, any of the above ranges can be combined with any other range.

[0044] In some embodiments of the present application, the amount of trimethylpentyltriethoxysilane is 1-5 parts by weight, because the molecular structure of the polymer material is like a long line, which has low strength, is easy to break, and has no elasticity when not cross-linked. The role of the cross-linking agent is to produce chemical bonds between linear molecules, so that the linear molecules are connected to each other to form a network structure, which can improve strength and elasticity. In the present application, trimethylpentyltriethoxysilane plays such a role. When the amount is too low (less than 1 part), the elasticity and strength of the coating will be weakened, its durability will be reduced, the coating will be easy to crack, the adhesion will decrease, and the protective performance will be weakened; when the amount is too high (more than 5 parts), the coating becomes too hard and brittle, reducing its impact resistance, causing the coating to crack easily when the temperature changes, affecting the protective performance. Therefore, the amount of trimethylpentyltriethoxysilane can be 1 part, 3 parts, 5 parts, etc., as well as all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.

[0045] In some embodiments of the present application, the organic solvent is a D40 solvent. The solubility of the solvent is less than 0.1%, and it has the properties of strong solubility, good volatility, good stability, low sulfur, low aromaticity, and easy volatility. The use of other organic solvents may result in an unstable coating system, poor dispersibility, and obvious unevenness after coating. At the same time, the amount of organic solvent should also be controlled. Too little will affect the solubility and construction of the coating, causing the coating to be too thick and difficult to construct, affecting the construction quality and uniformity of the coating; while too much will cause the coating to dry too fast and the surface to be uneven. These uneven surfaces are often more prone to cracks, affecting the appearance and protective performance. Therefore, the amount of organic solvent used is 10 parts, 20 parts, 30 parts, etc., and all ranges and sub-ranges between the above values. It should be understood that in the implementation scheme, any of the above ranges can be combined with any other range.

[0046] In some embodiments of the present application, the inorganic filler is one or more of titanium dioxide, heavy calcium, and mica. If the amount of inorganic filler is too low (less than 20 parts), the covering power and wear resistance of the coating will be insufficient; but if it is too high (more than 35 parts), the viscosity of the coating will increase, affecting the workability, and also adversely affecting the flexibility and adhesion of the coating. Therefore, the total amount of inorganic filler can be 20 parts, 21 parts, 22 parts, 24 parts, 25 parts, 27 parts, 28 parts, 29 parts, 30 parts, 32 parts, 33 parts, 35 parts, etc., and all ranges and sub-ranges between the above values. At the same time, among the inorganic fillers described in the present application, titanium dioxide, heavy calcium, and mica can be used alone or in combination. More preferably, the three are mixed. Among them, for high-cold and high-altitude areas, titanium dioxide can be selected as the main filler, mica and heavy calcium can be used as auxiliary, titanium dioxide can provide high hiding power and weather resistance, especially UV resistance, and the proportion of titanium dioxide can be appropriately increased to further enhance the weather resistance and antifreeze performance of the coating; mica can provide additional barrier effect and high gloss, while improving antifreeze performance, especially in high humidity and large temperature difference environments; heavy calcium can reduce costs and provide certain rheological and chemical stability, but considering that the coating described in this application is used in high-cold and high-altitude areas, the amount of heavy calcium should be appropriately reduced to ensure the high performance of the coating. Therefore, in the inorganic filler described in this application, the amount of the three is calculated by weight as follows: titanium dioxide is 15-25 parts to ensure high hiding power and weather resistance, especially under high UV radiation and low temperature conditions; heavy calcium is 10-15 parts to ensure cost-effectiveness and rheology, but the amount should not be too much to avoid affecting the high performance of the coating; mica is 10-15 parts to provide barrier effect and high gloss, while enhancing antifreeze performance. It should be understood that in embodiments, any of the above ranges may be combined with any other ranges.

[0047] In some embodiments of the present application, the auxiliary agent includes a wetting agent, a dispersant and a defoaming agent; wherein the wetting agent is PE-100. The use of this wetting agent has a very strong wetting effect on various pigments and fillers in an aqueous system, can reduce surface tension, make the solid surface easy to wet, and shorten the grinding and dispersion time; it is especially effective for the hydrophobic particles described in the present application. PE-100 can also avoid the coagulation of pigments and fillers and enhance stability; in addition, it can also be used as a color enhancer for latex knees and a color adhesive for color coatings, which helps to overcome the disadvantages of floating color, blooming, etc., and effectively eliminates various coating defects caused by the use of defoaming agents. It is preferred for the technical solution described in the present application. The dispersant is ammonium salt dispersant 5027 or 5040. Both dispersants have excellent properties, can reduce the viscosity of the grinding material, improve the storage stability of the coating, increase the gloss and leveling properties, etc.; at the same time, compared with other dispersants, these two dispersants have better dispersing effects for this application, can obtain very excellent dispersing effects at a lower dosage, and also help to improve the water resistance of the coating, and can also keep the viscosity of the coating obtained after the raw materials are mixed unchanged, so that the coating has better stability. The defoamer is KMT-7033, which is a silicone defoamer that is universal for water and oil, has extremely strong bubble breaking and anti-foaming capabilities, and has extremely high efficiency. It has a good effect at a very low addition amount, and is particularly suitable for eliminating microbubbles in high-viscosity coatings and ink systems; and because it is a self-emulsifying defoamer, it needs to be added during the grinding stage, and is particularly suitable for the preparation of water-based color pastes. Among them, calculated according to the total mass of the coating, the amount of the wetting agent is 2% to 2.5%, the amount of the dispersant is 3.5% to 4.5%, and the amount of the defoaming agent is 0.5% to 1%. The additives used in the subsequent examples and comparative examples of this application are used according to this ratio.

[0048] 2. A method for preparing a bio-based coating that extends the durability of concrete surfaces in cold and high-altitude areas

[0049] Step 1: Preparation of impregnated bio-based siloxane

[0050] Add isopropanol, methyltriethoxysilane, heptadecafluorodecyltrimethoxysilane, γ-aminopropyltriethoxysilane, polyoxyethylene mono-4-octylphenyl ether, ethyl orthosilicate and acetic acid to the reactor in sequence, raise the temperature to 110°C, then stir for 35 hours, reduce the temperature to 100°C, then stir for 35 hours; control the pH value to 7; reduce the temperature to 50°C, keep the temperature at this temperature for 2 hours, add the film-forming agent and continue stirring for 3 hours to obtain an impregnated bio-based siloxane;

[0051] Among them, the amount of raw materials calculated by weight is as follows: 3-5 parts of methyltriethoxysilane, 3-5 parts of heptadecafluorodecyltrimethoxysilane, 3-5 parts of γ-aminopropyltriethoxysilane, 3-5 parts of polyoxyethylene mono-4-octylphenyl ether, 3-7 parts of tetraethyl orthosilicate, 1-2 parts of acetic acid, 90-100 parts of isopropanol, and 2-3 parts of film-forming agent.

[0052] Step 2: Preparation of hydrophobic silica biomicrospheres

[0053] S1: dissolving polyvinyl alcohol, di-tert-butyl-p-cresol and sodium sulfate in ultrapure water to prepare an aqueous phase solution; wherein the mass ratio of polyvinyl alcohol, di-tert-butyl-p-cresol and sodium sulfate is (20-25): (0.1-0.5): (0.2-0.5);

[0054] S2: uniformly mixing an organic peroxide initiator, vinyl chloride, divinylbenzene, D40 solvent oil and an acetylene glycol surfactant until they are completely dissolved to obtain an oil phase solution; wherein the mass ratio of the organic peroxide initiator, vinyl chloride, divinylbenzene, D40 solvent oil and the acetylene glycol surfactant is (2.5-3.0):(5-10):(1-5):(1-2):(3-5);

[0055] S3: The oil phase is uniformly dispersed in the water phase to prepare an O / W emulsion, and a suspension polymerization reaction is carried out under a nitrogen atmosphere at a reaction temperature of 80 to 90° C. for a reaction time of 10 to 14 hours, followed by washing and drying to obtain the hydrophobic silica biomicrospheres.

[0056] Step 3: Use the above raw materials and mix them evenly according to the following components:

[0057] Calculated by weight, the impregnated bio-based siloxane is 20-30 parts, the silicon coupling agent is 1-2 parts, the hydrophobic silicon biomicrospheres are 10-20 parts, the deionized water is 15-20 parts, the inorganic filler is 20-35 parts, the auxiliary agent is 5-15 parts, the anti-aging agent is 1-5 parts, the trimethylpentyltriethoxysilane is 1-5 parts, the bio-based composite antibacterial agent is 1-5 parts, and the organic solvent is 10-30 parts.

[0058] Step 4: Apply the coating obtained by mixing in step 3 on the clean and dry concrete surface, and allow it to solidify after contact with air.

[0059] 3. Examples and Comparative Examples

[0060] 1. Preparation of impregnated bio-based siloxane

[0061] Example 1

[0062] Calculated by weight, the following raw materials are used:

[0063] 3 parts of methyltriethoxysilane, 3 parts of heptadecafluorodecyltrimethoxysilane, 3 parts of γ-aminopropyltriethoxysilane, 3 parts of polyoxyethylene mono-4-octylphenyl ether, 3 parts of ethyl orthosilicate, 1 part of acetic acid, 90 parts of isopropanol, and 2 parts of film-forming agent.

[0064] Isopropanol, methyltriethoxysilane, heptadecafluorodecyltrimethoxysilane, γ-aminopropyltriethoxysilane, polyoxyethylene mono-4-octylphenyl ether, ethyl orthosilicate and acetic acid were added to the reactor in sequence, the temperature was raised to 110°C, followed by stirring for 35 hours, the temperature was lowered to 100°C, followed by stirring for 35 hours; the pH value was controlled to be 7; the temperature was lowered to 50°C, kept at this temperature for 2 hours, and then a film-forming agent was added and stirring was continued for 3 hours to obtain an impregnated bio-based siloxane.

[0065] Example 2

[0066] Calculated by weight, the following raw materials are used:

[0067] 4 parts of methyltriethoxysilane, 4 parts of heptadecafluorodecyltrimethoxysilane, 4 parts of γ-aminopropyltriethoxysilane, 4 parts of polyoxyethylene mono-4-octylphenyl ether, 5 parts of ethyl orthosilicate, 1.5 parts of acetic acid, 95 parts of isopropyl alcohol, and 2.5 parts of film-forming agent.

[0068] Isopropanol, methyltriethoxysilane, heptadecafluorodecyltrimethoxysilane, γ-aminopropyltriethoxysilane, polyoxyethylene mono-4-octylphenyl ether, ethyl orthosilicate and acetic acid were added to the reactor in sequence, the temperature was raised to 110°C, followed by stirring for 35 hours, the temperature was lowered to 100°C, followed by stirring for 30 hours; the pH value was controlled to be 7; the temperature was lowered to 50°C, kept at this temperature for 2 hours, and then a film-forming agent was added and stirring was continued for 4 hours to obtain an impregnated bio-based siloxane.

[0069] Example 3

[0070] Calculated by weight, the following raw materials are used:

[0071] 5 parts of methyltriethoxysilane, 5 parts of heptadecafluorodecyltrimethoxysilane, 5 parts of γ-aminopropyltriethoxysilane, 5 parts of polyoxyethylene mono-4-octylphenyl ether, 7 parts of ethyl orthosilicate, 2 parts of acetic acid, 100 parts of isopropanol, and 3 parts of film-forming agent.

[0072] Isopropanol, methyltriethoxysilane, heptadecafluorodecyltrimethoxysilane, γ-aminopropyltriethoxysilane, polyoxyethylene mono-4-octylphenyl ether, ethyl orthosilicate and acetic acid were added to the reactor in sequence, the temperature was raised to 110°C, followed by stirring for 35 hours, the temperature was lowered to 100°C, followed by stirring for 35 hours; the pH value was controlled to be 8; the temperature was lowered to 50°C, kept at this temperature for 2 hours, and then a film-forming agent was added and stirring was continued for 4 hours to obtain an impregnated bio-based siloxane.

[0073] 2. Preparation of hydrophobic silica biomicrospheres

[0074] Example 4

[0075] S1: dissolving polyvinyl alcohol, di-tert-butyl-p-cresol and sodium sulfate in ultrapure water to prepare an aqueous phase solution; wherein the mass ratio of polyvinyl alcohol, di-tert-butyl-p-cresol and sodium sulfate is 20:0.1:0.2;

[0076] S2: uniformly mixing the organic peroxide initiator, vinyl chloride, divinylbenzene, D40 solvent oil and acetylene glycol surfactant until they are completely dissolved to obtain an oil phase solution; wherein the mass ratio of the organic peroxide initiator, vinyl chloride, divinylbenzene, D40 solvent oil and acetylene glycol surfactant is 2.5:5:1:1:3;

[0077] S3: The oil phase is uniformly dispersed in the water phase to prepare an O / W emulsion, and a suspension polymerization reaction is carried out under a nitrogen atmosphere at a reaction temperature of 80° C. for a reaction time of 10 h, followed by washing and drying to obtain the hydrophobic silica biomicrospheres.

[0078] Example 5

[0079] Adjustments are made based on Example 4, except that:

[0080] S1: The mass ratio of polyvinyl alcohol, di-tert-butyl-p-cresol and sodium sulfate is 23:0.4:0.3;

[0081] S2: The mass ratio of organic peroxide initiator, vinyl chloride, divinylbenzene, D40 solvent oil and acetylene glycol surfactant is 2.7:8:3:1.5:4;

[0082] S3: The reaction temperature is 85°C and the reaction time is 12h.

[0083] The other steps are exactly the same as those in Example 4 to obtain the hydrophobic silica biomicrospheres.

[0084] Example 6

[0085] Adjustments are made based on Example 4, except that:

[0086] S1: the mass ratio of polyvinyl alcohol, di-tert-butyl-p-cresol and sodium sulfate is 25:0.5:0.5;

[0087] S2: The mass ratio of organic peroxide initiator, vinyl chloride, divinylbenzene, D40 solvent oil and acetylene glycol surfactant is 3:10:5:2:5;

[0088] S3: The reaction temperature is 90°C and the reaction time is 14h.

[0089] The other steps are exactly the same as those in Example 4 to obtain the hydrophobic silica biomicrospheres.

[0090] 2. Preparation of the coating

[0091] Table 1 Types of various raw materials

[0092]

[0093]

[0094] Note: -- indicates that the component is not added.

[0095] Table 2 Amount of each component

[0096]

[0097] The examples and comparative examples focus on the effects of the amounts of siloxane, coupling agent, microspheres and trimethylpentyltriethoxysilane on the properties of the coating. The effects of the amounts of other components on the properties of the coating have been recorded in the aforementioned content. The amounts of each component in Examples 10 to 15 are exactly the same as in Example 1; the amounts of each component in Comparative Examples 4 to 7 are exactly the same as in Example 1, and in Comparative Example 7, without the addition of siloxane and microspheres, the amounts of other raw materials are exactly the same as in Example 1; the types of siloxane, microspheres, silicon coupling agents and organic solvents in Comparative Examples 8 to 13 are exactly the same as in Example 1, and the amounts of each component are adjusted based on Example 1, and the other steps are exactly the same as in Example 1.

[0098] The coatings prepared in the examples and comparative examples were tested for performance using the standard GB / T 50082-2009 Long-term performance and durability test method for ordinary concrete (freeze-thaw resistance (temperature change resistance), impermeability) / GB / T 1741-2020 Determination of mildew resistance of paint films (mildew resistance) / HG / T 3792-2014 cross-linked fluororesin coatings (other indicators), and the results are shown in Tables 3 and 4. Considering that the present application is used in high-cold and high-altitude areas, the time of resistance to artificial weathering is calculated based on how many hours after the coating begins to show obvious discoloration, powdering, cracking, peeling, etc. after the QUV accelerated aging test.

[0099] Table 3 Performance test results of materials in embodiments and comparative examples

[0100]

[0101] Table 4 Performance test results of materials in embodiments and comparative examples

[0102]

[0103]

[0104] From Tables 1 to 4, we can see that:

[0105] (1) The embodiments all have excellent performance, especially in terms of resistance to artificial weathering, mildew resistance and impermeability, which are far superior to the comparative examples. In order to verify the effect in practical applications, the present application built an experimental building in a certain area of ​​Tibet, and coated the embodiments and comparative examples on its surface for performance comparison. From October 2023 to the present, the surface of the embodiment coating has not shown any aging, cracking, shedding and mildew growth. The surface of the building coated with the embodiment is intact and does not affect the beauty of the building. The comparative examples have different degrees of mildew, aging and shedding, especially in high-altitude and cold areas with large temperature differences between day and night. When the temperature changes significantly, the number of cracks on the coating surface of the building coated with the comparative example coating will increase significantly, and even part of the coating surface will fall off.

[0106] (2) It can be seen from Example 7 and Comparative Examples 1-2 that when the amount of the impregnated bio-based siloxane prepared by the method described in the present application is reduced, the water resistance and freeze-thaw resistance of Comparative Example 1 decrease significantly. This is because the less the amount of the impregnated bio-based siloxane used, the greater the elastic modulus and water absorption rate of the silicone coating, and it is unable to prevent water and chloride ions from penetrating into the coating. When the amount of the impregnated bio-based siloxane used is too much, its water resistance is not as good as that of Comparative Example 1. This is because too much use will lead to an increase in the silane content, and the Shore hardness and water contact angle will decrease, thereby making the coating formed in Comparative Example 2 more susceptible to erosion, and the freeze-thaw resistance effect is significantly worse than that of Example 7. Furthermore, the fungus resistance of Comparative Examples 1 and 2 decreases significantly, especially Comparative Example 2. This is because the excessive amount of silane added leads to an increase in the hydrophilic groups on the coating surface, a decrease in the water contact angle, and a significant increase in the amount of mold and bacteria attached. Comparative Examples 1 and 2 are more susceptible to mildew than Example 7 in a high-altitude environment.

[0107] (3) Comparative Examples 4 and 6 showed stratification within a short period of time after stirring, which indicates that other siloxanes purchased on the market are not compatible with the coating system described in the present application, and it is difficult to form a coating system that can be used for coating, so other properties cannot be tested; Comparative Example 5 uses ordinary microsphere materials purchased on the market, and its water resistance, freeze-thaw resistance and impermeability are all worse than those of the embodiments.

[0108] (4) In Comparative Examples 8 and 9, the dosage of silicon coupling agent was adjusted. The water resistance and freeze-thaw resistance of Comparative Example 8 decreased significantly. The coating of Comparative Example 8 was prone to cracking and its adhesion decreased. After one month of actual application, very obvious cracks appeared, and its protective effect was also significantly affected. The dosage of coupling agent in Comparative Example 9 was too high, resulting in excessive crosslinking inside the system. In actual application, the coating became too hard and brittle, and was more prone to cracking than Comparative Example 8. Especially when the temperature changed, the number of cracks on the surface of the coating of Comparative Example 9 increased more than that of Comparative Example 8, and even powdering and slagging occurred.

[0109] (5) Comparative Examples 10 and 11 adjusted the dosage of microspheres. The dosage of microspheres in Comparative Example 10 was too small to provide sufficient hydrophobicity, resulting in a decrease in the waterproof performance of the coating. Its water resistance and freeze-thaw resistance were even worse than those of Comparative Example 11. In actual application, after the same period of time, mold appeared on the surface of the coating of Comparative Example 10 earlier than that of Comparative Example 11, and the area of ​​mold was much larger than that of Comparative Example 11. In Comparative Example 11, due to the excessive dosage of microspheres, the dispersibility of the coating was affected, which resulted in defects such as flowery phenomenon on the surface of the coating, and the coating surface was obviously uneven, which seriously affected the appearance. At the same time, compared with Example 1, its various properties also declined to a certain extent.

[0110] (6) Comparative Examples 12 and 13 adjusted the amount of trimethylpentyltriethoxysilane used. The elasticity and strength of the coating of Comparative Example 12 were weakened, which caused a significant decrease in the adhesion and other properties of Comparative Example 12. In actual applications, the coating of Comparative Example 12 was the first to crack among all the comparative examples and had the worst protective performance. The coating of Comparative Example 13 was too hard and brittle. Although the adhesion was good, the number of cracks on the coating surface also increased significantly when the temperature changed greatly.

[0111] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the technical solution. Ordinary technicians in this field should understand that those modifications or equivalent substitutions of the technical solution of the present application that do not depart from the purpose and scope of the technical solution of the present application should be included in the scope of the claims of the present application.

Claims

1. A bio-based coating for extending the durability of concrete surface in cold and high altitude areas, characterized in that: Calculated by weight, the coating comprises the following components: The impregnated bio-based siloxane is 20-30 parts, the silicon coupling agent is 1-2 parts, the hydrophobic silicon bio-microspheres are 10-20 parts, the deionized water is 15-20 parts, the inorganic filler is 20-35 parts, the auxiliary agent is 5-15 parts, the anti-aging agent is 1-5 parts, the trimethylpentyltriethoxysilane is 1-5 parts, the bio-based composite antibacterial agent is 1-5 parts, and the organic solvent is 10-30 parts.

2. The coating according to claim 1, characterized in that: The impregnated bio-based siloxane is prepared by the following method: Add isopropanol, methyltriethoxysilane, heptadecafluorodecyltrimethoxysilane, γ-aminopropyltriethoxysilane, polyoxyethylene mono-4-octylphenyl ether, ethyl orthosilicate and acetic acid to the reactor in sequence, raise the temperature to 110°C, then stir for 35 hours, reduce the temperature to 100°C, then stir for 35 hours; control the pH value to 7; reduce the temperature to 50°C, keep the temperature at this temperature for 2 hours, add the film-forming agent and continue stirring for 3 hours to obtain an impregnated bio-based siloxane; Among them, the amount of raw materials calculated by weight is as follows: 3-5 parts of methyltriethoxysilane, 3-5 parts of heptadecafluorodecyltrimethoxysilane, 3-5 parts of γ-aminopropyltriethoxysilane, 3-5 parts of polyoxyethylene mono-4-octylphenyl ether, 3-7 parts of tetraethyl orthosilicate, 1-2 parts of acetic acid, 90-100 parts of isopropanol, and 2-3 parts of film-forming agent.

3. The coating according to claim 1, characterized in that: The silicon coupling agent is one of an aminosilane coupling agent, a silicate coupling agent, a silicon oxide coupling agent, and a fluorocarbon silane coupling agent.

4. The coating according to claim 1, characterized in that: The hydrophobic silica biomicrospheres are obtained by the following method: Step 1: dissolving polyvinyl alcohol, di-tert-butyl-p-cresol and sodium sulfate in ultrapure water to prepare an aqueous phase solution; wherein the mass ratio of polyvinyl alcohol, di-tert-butyl-p-cresol and sodium sulfate is (20-25): (0.1-0.5): (0.2-0.5); Step 2: uniformly mixing an organic peroxide initiator, vinyl chloride, divinylbenzene, D40 solvent oil and an acetylene glycol surfactant until they are completely dissolved to obtain an oil phase solution; wherein the mass ratio of the organic peroxide initiator, vinyl chloride, divinylbenzene, D40 solvent oil and the acetylene glycol surfactant is (2.5-3.0):(5-10):(1-5):(1-2):(3-5); Step 3: Evenly disperse the oil phase in the water phase to prepare an O / W emulsion, and carry out a suspension polymerization reaction under a nitrogen atmosphere at a reaction temperature of 80 to 90° C. for a reaction time of 10 to 14 hours, and then wash and dry to obtain the hydrophobic silica biomicrospheres.

5. The coating according to claim 1, characterized in that: The bio-based composite antimicrobial agent is Composite antimicrobial agent.

6. The coating according to claim 1, characterized in that: The organic solvent is one of aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, halogenated hydrocarbons, alcohols, esters, ketones, and glycol derivatives, or a mixture of several of them.

7. The coating according to claim 1, characterized in that: The inorganic filler is one or more of titanium dioxide, heavy calcium and mica.

8. The coating according to claim 1, characterized in that: The auxiliary agent includes a wetting agent, a dispersant and a defoaming agent; wherein the wetting agent is PE-100, the dispersant is an ammonium salt dispersant 5027 or 5040 dispersant, and the defoaming agent is KMT-7033.

9. A method for preparing a bio-based coating for extending the durability of concrete surfaces in cold and high altitude areas, characterized in that: The preparation of the coating according to any of claims 1 to 8 comprises the following steps: Step 1: uniformly mix the raw materials of the coating according to any one of claims 1 to 8; Step 2: Apply the coating obtained by mixing in step 1 on the clean and dry concrete surface, and allow it to solidify after contact with air.